Fundamental Research in Electrical Engineering The Selected Papers of The First International Conference on Fundamental Research in Electrical Engineering - Montaser Kouhsari, Shahram; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume presents the selected papers of the First International Conference on Fundamental Research in Electrical Engineering, held at Khwarazmi University, Tehran, Iran in July, 2017. The selected papers cover the whole spectrum of the main four fields of Electrical Engineering (Electronic, Telecommunications, Control, and Power Engineering).
Keywords: Telecommunication; Electric power production; Communications Engineering, Networks; Microwaves, RF Engineering and Optical Communications; Electrical Power Engineering